Instagram @Motivasii_Hijrahh_ Sebagai Media Dakwah Dalam Peningkatan Pengalaman Beragama Remaja Masjid Kampung Rawa Sugi - Kharismawati, Siti Hanifah; sari, Fatma; Maseni, Maseni (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
This thesis is a research on Instagram @motivasii_hijrahh_ as a Da'wah Media in Improving the Religious Experience of Youth at Kampung Rawa Sugi Mosque. The type of research used is qualitative research with a mass communication approach and a da'wah approach. There are two sources of data in this study, namely primary data sources and secondary data sources. The results of this study can be concluded that the effectiveness of Instagram as a social media in preaching is considered capable of touching various groups, including teenagers, to adults. Through social media, da'wah can be conveyed better than da'wah through Islamic events. Because the da'wah delivered can be directly read or known by millions of people at the same time. Through social media, da'wah activities become easier. The Instagram account @motivasii_hijrahh_ preaches through Instagram by using features on Instagram such as photos/quotes, videos and instastories. The Instagram account @motivasii_hijrahh_ has a positive impact on mosque youth in Rawa Sugi village who are followers of the @motivasii_hijrahh_ account. And of course it can add to the religious experience for mosque youth in Rawa Sugih village. Da'wah in the mass media is said to be effective because it is able to have a positive impact. The impact of mass communication in three aspects namely cognitive effects, affective effects and conative/behavioral effects. The motivational_hijrahh_ Instagram account has a positive impact and has cognitive, affective and behavioral effects on increasing the religious experience of adolescents at the Rawa Sugi village mosque.